Endophytic colonisation of tomato by the entomopathogenic fungus Beauveria bassiana: the use of different inoculation techniques and their effects on the tomato leafminer Tuta absoluta (Lepidoptera: Gelechiidae) - Natalia Allegrucci (Journal of Plant Protection Research, 2017)
Fungal entomopathogens can naturally regulate populations of various insects. The entomopathogen Beauveria bassiana (Bals.- Criv.) Vuill. is also able to endophytically colonize different plants. Endophytic colonization by entomopathogens may provide a source of indirect interactions between fungi and insects and has been associated with the ability of the fungus to control insect pests. The tomato leaf miner, Tuta absoluta (Meyrick) is considered one of the most devastating pests of tomato (Solanum lycopersicum L.) and its difficult control is due to its miner habit, short life cycle, and high reproductive capacity. The aims of this study were: (i) to use three different techniques, i.e. leaf spraying, seed immersion and root dipping, for the endophytic inoculation of B. bassiana in tomato plants; and (ii) to assess the effect of B. bassiana on tomato leaf consumption and mortality of T. absoluta after inoculation. The percentage of colonization by B. bassiana was assessed 7, 14 and 28 days after inoculation. All inoculation techniques employed allowed the recovery of B. bassiana, although our results showed significant differences between techniques. Leaf spraying was the most effective, with the highest percentage of colonization recorded 7 days after inoculation. We also evaluated (i) the effect on the mortality of T. absoluta by direct contact with conidia of B. bassiana, and (ii) the effect on tomato leaf consumption and mortality by indirect contact through ingestion of inoculated plant tissues with B. bassiana. Mortality bioassays showed that B. bassiana infected T. absoluta, either by direct contact or indirectly, via ingestion of inoculated tomato leaves. Direct contact showed a higher percentage of mortality and a lower median survival time (MST) than indirect contact. Significant differences in the mortality percentages of T. absoluta after exposure with B. bassiana were found among the treatments and the control. Our results suggest that the endophytic inoculation of B. bassiana in tomato crops provides the basis for further investigation, which should focus on the virulence of the endophytic B. bassiana against T. absoluta.